2018
DOI: 10.1016/j.juro.2017.08.112
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Predictors of Parastomal Hernia after Robot-Assisted Radical Cystectomy and Ileal Conduit Urinary Diversion

Abstract: Symptoms develop in approximately a third of patients with parastomal hernia and 15% will require surgery. The risk of parastomal hernia plateaued after postoperative year 3. Longer operative time, a larger fascial defect and lower postoperative kidney function were associated with parastomal hernia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 29 publications
2
39
3
Order By: Relevance
“…After removing duplicates, screening titles and abstracts, and evaluating full texts, 15 (9,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) of 469 studies containing 4,252 patients were included to evaluate the incidence of PH after RC and IC. The studied population came from USA (9,12,14,15,18,20,24,25), China (22), Switzerland (23), Denmark (13), Japan (16,17), Spain (19), and Sweden (21). The vast majority of articles were reported retrospectively, and the span of median time to diagnosis of PH was from 11 to 28.8 months.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicates, screening titles and abstracts, and evaluating full texts, 15 (9,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) of 469 studies containing 4,252 patients were included to evaluate the incidence of PH after RC and IC. The studied population came from USA (9,12,14,15,18,20,24,25), China (22), Switzerland (23), Denmark (13), Japan (16,17), Spain (19), and Sweden (21). The vast majority of articles were reported retrospectively, and the span of median time to diagnosis of PH was from 11 to 28.8 months.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…They observed that 80% (1/5) of initial type 1 hernias progressed to type 3 while 33% (30/90) of initial type 2 hernias progressed to type 3. In addition, Hussein et al (12) reported that 32% patients developed PH after robot-assisted RC (RARC) and IC at 3 years. PH-related symptoms, such as pain, bowel incarceration, appliance difficulties, discomfort, or PH-induced leakage, were reported in six studies (9,12,14,16,19,20), and the incidence rate ranged from 15% to 44%.…”
Section: Incidencementioning
confidence: 99%
“…It is noteworthy that no cases of parastomal hernia were observed. Hussein et al [35] reported that the incidence of parastomal hernia after RC and IC was as high as 20%, of which 15% patients required surgery. The absence of parastomal hernia in this study was mainly due to our modi cations.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of prospective data about the natural history and trajectory of PSH and whether PSH severity progression can be arrested [ 8 , 9 ]. PSH can be repaired surgically but results to date have been disappointing, with reported recurrence rates of 30 to 76% [ 10 ].…”
Section: Introductionmentioning
confidence: 99%